Animal health and welfare for sustainable livestock systems - Magnusson, Ulf; Boqvist, S.; Doyle, Rebecca; Robinson, T. (Global Agenda for Sustainable Livestock, 2022)
Over the last 30 years, the consumption of meat, milk and eggs in low- and middle-income (LMICs) countries has more than doubled (FAOSTAT, accessed 28/5/21). Population growth, urbanization, income gains and globalization continue to fuel the growth. Many people in LMICs do not have sufficient high quality protein in their diets (FAO et al., 2020); a problem that could be rectified through improved access to animal-source foods. Many in high- income countries (HICs), conversely, eat too much animal-sourced foods. Policies and information campaigns should promote healthy diets for all.